Likeable social media : how to delight your customers, create an irresistible brand, and be generally amazing on facebook (& other social networks) - Kerpen, Dave (McGraw-Hill, 2011)
In Likeable Social Media, Dave Kerpen reveals the secrets to building a brand's popularity by being authentic, engaging, and transparent on Facebook and other social media sites. He shares the methods he has used to successfully redefine the brands of a number of large companies, including 1-800-FLOWERS and Cumberland Farms. Complete with serious strategies communicated with wit and humor, this book is the definitive source for using social media to win new customers, gather valuable feedback, and increase the bottom line. Description from http://www.mheducation.asia (June 13, 2012.)